Improving the efficiency of phosphate rocks combined with phosphate solubilizing Actinomycetota to increase wheat growth under alkaline and acidic soils - Boubekri, Kenza; Soumare, Abdoulaye; Lyamlouli, Karim; Ouhdouch, Yedir; Hafidi, Mohamed; Kouisni, Lamfeddal (Frontiers in Plant Science, 2023)
Low availability of phosphorus (P) in both acidic and alkaline soils is a major problem for sustainable improvement in wheat crops yield. Optimization of crops productivity can be achieved by increasing the bioavailability of P by phosphate solubilizing Actinomycetota (PSA). However, their effectiveness may vary with changing agro-climatic conditions. In this regard, a greenhouse experiment was conducted to assess the interaction inoculation of five potential PSA (P16-P18-BC3-BC10 and BC11) and RPs (RP1- RP2-RP3 and RP4) on the growth and yield of wheat crop in unsterilized P- deficient alkaline and acidic soils. Their performance was compared with single super phosphate (TSP) and reactive RP (BG4). The in-vitro tests showed that all PSA colonize wheat root and form a strong biofilm except Streptomyces anulatus strain P16. Our findings revealed that all PSA significantly improve the shoot/root dry weights, spike biomass, chlorophyll contents as well as nutrients uptake in plants fertilized with RP3 and RP4. However, the combined application of Nocardiopsis alba BC11 along with RP4 in alkaline soil, was effective in optimizing wheat yield attributes and improve the yield biomass up to 19.7% as compared to the triple superphosphate (TSP). This study supports the view that the inoculation with Nocardiopsis alba BC11 has a broad RP solubilization and could alleviate the agricultural losses due to P limitation in acidic and alkaline soils.